Evaluation of Principals' Performance in Improving The Quality of Graduates of State Vocational High Schools in Rejang Lebong - Sumarsih, Sumarsih; Sahara, Mella (Universitas Ahmad Dahlan, 2024)
The principal plays a crucial role in the successful attainment of school objectives. The role of principal leadership is crucial in enhancing school performance and promoting progress. The aim of the research is to evaluate the performance of school principals in improving the quality of graduates of vocational in high school. The research method uses a goal-oriented evaluation type of evaluation model. The research subjects were school principals, teachers, administrative staff, and students. Collecting data using interview techniques, observation and documentation studies. the data was analyzed quantitatively. Research results a. The performance of school principals has carried out innovations by managing change by creating innovations in achieving targets and student quality in the very good category. b) The performance of school principals in cultivating a creative, competitive work culture and a comfortable, healthy work climate is in the good category, c) The performance of school principals in utilizing information technology in learning and developing library systems that support the quality of learning is in the very good category. Suggestions to school principals can facilitate and support teacher creativity in implementing innovative learning models